If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2(x + 1) = 12 Reorder the terms: 9x + -2(1 + x) = 12 9x + (1 * -2 + x * -2) = 12 9x + (-2 + -2x) = 12 Reorder the terms: -2 + 9x + -2x = 12 Combine like terms: 9x + -2x = 7x -2 + 7x = 12 Solving -2 + 7x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7x = 12 + 2 Combine like terms: -2 + 2 = 0 0 + 7x = 12 + 2 7x = 12 + 2 Combine like terms: 12 + 2 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 0=(3x-8)*lnx | | n+8=16-4 | | -6(x-7)-7=35 | | 8(2w-6)+7(-y+5)=-8 | | n+5=13-8 | | Log(16)32-log(16)2=x | | 3p^2-5p=4p^2-35p+56 | | 2(x-4)=2x+3x | | 12(s+5)=7.5 | | 20x-2=36x+2 | | n^2+8n-7=0 | | 7w^2+3=-10w | | 36=16x-12x | | 4(2x)=40 | | 3x^2+x-0.5=0 | | 2(3x)=36 | | 10x+6y=16 | | -7x^2-18x+0=0 | | 2z-67=-21 | | 8-(-4)+5=12 | | 7n+3-5n=3n-6 | | V=3.14v^2h | | (25)(7)+x=175 | | -3x+6x=0 | | 0=5x^2-64x-13 | | 18+5=48 | | x-29=15 | | .5(12x-8)=9x-18 | | 5x-3-2x=2(x-4) | | 3(x+2)=5(x-1)+5 | | 0=2a^2+7a+3 | | 4(5y-3)-(8y+5)= |